Microsurgical Anatomy of the Jugular Foramen Applied to Surgery of Glomus Jugulare via Craniocervical Approach - Constanzo, Felipe; Coelho Neto, Mauricio; Nogueira, Gustavo Fabiano; Ramina, Ricardo (Frontiers in Surgery, 2020)
The jugular foramen remains one of the most complex regions of the human body. Approaching lesions in this area requires extensive anatomical knowledge and experience, due to the many critical neurovascular structures passing through or around the jugular foramen. Here, we present a concise review of the microsurgical anatomy of the jugular foramen in relation to the craniocervical approach.